Assessing the Adaptability of Quinoa and Millet in Two Agroecological Zones of Rwanda - Habiyaremye, Cedric; Ndayiramije, Olivier; D'Alpoim Guedes, Jade; Murphy, Kevin M. (Frontiers in Sustainable Food Systems, 2022)
Quinoa (Chenopodium quinoa Willd.) and millet species (including Eleusine coracana, Panicum miliaceum, and Setaria italica) are nutritionally valuable seed crops with versatile applications in food production and consumption. Both quinoa and millet have the potential to provide drought-tolerant, nutritious complementary crops to maize that is predominantly cultivated in Rwanda. This study evaluated quinoa and millet genotypes and assessed their agronomic performance in two agroecological zones of Rwanda. Twenty quinoa and fourteen millet cultivars were evaluated for grain yield, emergence, days to heading, flowering, and maturity, and plant height in 2016 and 2017 in Musanze, a highland region (2,254 m above sea level), and Kirehe, in the Eastern lowlands of Rwanda (1,478 m above sea level). Quinoa yield ranged from 189 to 1,855 kg/ha in Musanze and from 140 to 1,259 kg/ha in Kirehe. Millet yield ranged from 16 to 1,536 kg/ha in Musanze and from 21 to 159 kg/ha in Kirehe. Mean cultivar plant height was shorter in Kirehe (μ = 73 and 58 cm for quinoa and millets, respectively), than Musanze (μ = 93 and 76 cm for quinoa and millets, respectively). There was a genotype × environment interaction for maturity in quinoa and millet in both years. Across locations, “Titicaca” and “Earlybird” (Panicum miliaceum) were the earliest maturing quinoa and millet varieties, respectively, both with an average of 91 days to maturity. The results suggest that quinoa and millet have potential as regional crops for inclusion in the traditional dryland cropping rotations in Rwanda, thereby contributing to increased cropping system diversity and food security.